Targeting the D-series resolvin receptor system for the treatment of osteoarthritic pain - Huang, Junting; Burston, James J.; Li, Li; Ashraf, Sadaf; Mapp, Paul I.; Bennett, Andrew J.; Ravipati, Srinivasarao; Pousinis, Petros; Barrett, David A.; Scammell, Brigitte E.; Chapman, Victoria (Wiley, 2017)
Objective: Pain is a major symptom of osteoarthritis (OA); current analgesics either do not offer adequate pain relief or are associated with serious side effects. Herein we have investigated the therapeutic potential of targeting the resolvin receptor system to modify OA pain and pathology. Methods: Gene expression of two resolvin receptors (ALX and ChemR23) was quantified in synovia and medial tibial plateau collected from patients at joint replacement for OA. Two models of OA joint pain were used for mechanistic studies. Gene expression in the periphery and CNS were quantified. Effects of exogenous administration of the D-series resolvin precursor 17(R)-hydroxy Docosahexaenoic Acid (17(R)-HDoHE on pain behaviour, joint pathology, spinal microglia and astroglyosis were quantified. Plasma levels of relevant lipids, resolvin D2, 17R-HDoHE and arachidonic acid was determined in rats using LC-MS-MS. Results: There was a positive correlation between resolvin receptor and IL6 expression in human OA synovia and medial tibial plateau. In the rat, synovia gene expression of ALX was positively correlated with IL1β, TNFα and COX2. Treatment with 17(R)-HDoHE reversed established pain behaviour in two models of OA pain, but not joint pathology. This was associated with a significant elevation in plasma levels of resolvin D2 and a significant reduction in astrogliosis in the spinal cord in the MIA model. Conclusion: Our preclinical data demonstrate robust analgesics effects of activating the D series resolvin pathways in two different animal models of OA. Our data support a predominant central mechanism of action in this clinically relevant model of OA pain.